Contribution of the COVID-19 pandemic to the prognosis of patients with class III-IV heart failure - A. R. Vaisberg; I. V. Fomin; D. S. Polyakov; Yu. V. Omarova (Российский кардиологический журнал, 2022)
Aim. To study the survival of patients with New York Heart Association (NYHA) class IIIV heart failure (HF) after a coronavirus disease 2019 (COVID-19) and compare it with a group of similar patients without COVID-19, both during and before the pandemic.Material and methods. A sample of 810 patients with HF of any class was created, who were treated in the HF center at the City Clinical Hospital № 38 in Nizhny Novgorod for the period from March 2019 to March 2020. Patients with NYHA class HF III-IV (n=263) were selected from this sample. The diagnosis was confirmed by echocardiography and chest radiography. At the time of discharge, the 6-minute walk test was <300 meters, while the level of N-terminal pro-brain natriuretic peptide — >300 pg/ml. The group was analyzed from March 2019 to December 2021 with the definition of all-cause mortality depending on prior COVID-19.Results. During 520-day follow-up, 30,8% of NYHA class III-IV patients died, while 16,0% of patients underwent COVID-19, of which 79,25% of patients died during this period. Mortality among patients without prior COVID-19 was 23,3% (p<0,001). The 30-day mortality among those with COVID-19 was 50,0%, while for the year, this parameter was 71,4% (p<0,001). Among patients without COVID-19 and with class III-IV HF, 4,64% died in the first 30 days, and 20,7% of patients died during the year (p<0,001). The results obtained were compared with the data from the EPOCHA-CHF program from 2002 to 2017.Conclusion. Mortality among patients with class III-IV HF after COVID-19 was 3,5 times higher compared with those with class III-IV HF without prior COVID-19. During the COVID-19 pandemic, the mortality rate among patients with class III-IV HF without COVID-19 increased by 2,09 times compared with the pre-pandemic period.